Improving Reading Skills Of Beginning Deaf Students Through Global Reflective Maternal Methods Controlled Learning Motivation - Putri Kartika Ningsih; Mohammad Efendi; Ahmad Samawi (Journal of ICSAR, 2022)
Deaf students have barriers to listening skills, so they need appropriate and structured instruction for teaching early reading. Researchers combined MMR and the global method into the Global Reflective Maternal Method (MMG) for early reading learning for deaf students at the elementary level. Learning motivation needs to be owned by students both intrinsic and extrinsic. Through this research, the researcher wanted to know the effect of the application of MMG on the early reading skills controlled by the learning motivation of the basic level deaf students in SLB Kabupaten Madiun. The real experimental method (true experimental) was applied in this study with a pretest posttest control group design. The results pre-test of the initial reading skills of the control group had an average of 33.5 percent with less criteria, and the experimental group had an average of 28.6 percent with less criteria. The post test of the control group had an average of 32.8 percent with less criteria, and the experimental group had an average of 62.1 percent with sufficient criteria. Based on the significant test through t-test mean pre-test and post-test and compare the results of t-test with t-table 5 percent. The results of the significance test showed t equals 3.42 less than t table 5 percent equals 1.79 then the results were significant. Reinforced the results of the hypothesis test with the results of 3.42 less than 1.79 which means the Global Reflective Maternal Method (MMG) has an effect on the beginning reading skills of basic deaf students in SLB Kabupaten Madiun. The results of the observation of the learning motivation of the control group and the experimental group showed that the motivation of the experimental group was better than the control group. And when compared, the learning outcomes of the experimental group were higher than the control group.